Produção de grês porcelanato a partir de matérias-primas do estado da Bahia - Brito, Jorge Ferreira (2009)
The State Bahia, Brazil, presents different geological sites it with a very expressive variety minerals. It is situated among the very important States which produces minerals for industries, such as pointed aggregate, ornamentals stones and ceramics raw materials. Nowadays only four companies producting ceramics tiles. Porcelainized stoneware tiles is one of the noblest ceramics, depicting low water absorption (typically below of 0,5%), in addition to excellent staining resistance and mechanical strength. The present work aims at investigating the potential of local raw materials for the production of porcelainized stoneware tiles. For this purpose, these materials were characterized by X-ray fluorescence, X-ray diffraction, particle size analysis, thermal gravimetric analysis, thermal differential analysis and dilatometric analysis. Admixtures containing different compositions were prepared and fired at four temperatures, 1100 ºC, 1150 ºC, 1200 ºC and 1250 ºC with isotherm for 60 minute and heathing rate of 5 oC/min. After firing the samples, they were characterized by water absorption tests, linear retraction, analysis, apparent porosity, apparent specific mass, flexural strength, and microstructural analysis by X-ray diffraction and scanning electron microscopy . The results revealed three ceramics with porcelainized stoneware tiles characteristics and porcelain tile will be produce from raw materials originated in the State of Bahia